2022
DOI: 10.1016/j.heliyon.2021.e08686
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia medical students’ knowledge, attitudes, and practices toward COVID-19

Abstract: Implementing health protocols and preventive measures are the only effective ways to suppress COVID-19 transmission before vaccines and antiviral drugs are developed. The implementation of health protocols and preventive measures are influenced by one’s knowledge, attitudes, and practices (KAP) toward this pandemic. Medical students as candidates for healthcare workers and role models for the community should have a good KAP. This study intends 1) to explore the KAP of medical students in Indonesia toward COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 91 publications
3
41
1
4
Order By: Relevance
“…The institutional status of Higher Education where students were studying could significantly contribute to BK [H (1) = 17.465, p < 0.001] as well as DiCT [H (1) = 33.447 p < 0.001], in which scores of public university students were always significantly higher than those of private one. This fact was in line with the research of Sondakh et al (2022), informing that institutional status could influence students' competence (Hendajany, 2016). In addition, public and private universities in Indonesia were also reported to be different in terms of quality and regulation (Welch, 2007).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The institutional status of Higher Education where students were studying could significantly contribute to BK [H (1) = 17.465, p < 0.001] as well as DiCT [H (1) = 33.447 p < 0.001], in which scores of public university students were always significantly higher than those of private one. This fact was in line with the research of Sondakh et al (2022), informing that institutional status could influence students' competence (Hendajany, 2016). In addition, public and private universities in Indonesia were also reported to be different in terms of quality and regulation (Welch, 2007).…”
Section: Resultssupporting
confidence: 78%
“…(Fauzi et al, 2020). In addition, the other researchers also found that students' knowledge about the pandemic was still less satisfactory (Adli et al, 2022;Sondakh et al, 2022). Nevertheless, such a finding did not align with other foreign research showing that students could identify whichever information based on natural science falls into fake news about the COVID-19 (Puig et al, 2021).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Due to the urgency of the knowledge, attitudes, and practices (KAP) information during this current pandemic, several researchers have conducted KAP surveys with a variety of respondents. Some surveys involve the public ( Azlan et al, 2020 ; Chang et al, 2021 ) and other surveys involve healthcare students ( Sondakh et al, 2022 ; Zhang et al, 2021 ) and students from various majors ( Saefi et al, 2020 ). However, the research analyzing KAP about COVID-19 in Jordan is still limited.…”
Section: Introductionmentioning
confidence: 99%